2000
DOI: 10.1111/j.1553-2712.2000.tb01074.x
|View full text |Cite
|
Sign up to set email alerts
|

A Continuous Quality Improvement Approach to IL‐372 Documentation Compliance in an Academic Emergency Department, and Its Impact on Dictation Costs, Billing Practices, and Average Patient Length of Stay

Abstract: Abstract. Objective: To determine whether continuous quality improvement (CQI) methodology could improve and maintain IL-372 documentation compliance in an academic emergency department (ED). The impact on transcription costs, billing practices, and average patient length of stay was also analyzed. Methods: Baseline IL-372 compliance data were collected and shared with staff during a multidisciplinary educational session. Faculty dictation became mandatory. Pocket-sized dictation templates were provided. A Doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The most recent work employing QI is cited in Lovett et al [80] who reported an intervention at a multi-campus academic health system where immediate improvements were enhanced in relation to LOS. Other works employing QI can be seen in Brent et al [76], Fernandes and Christenson [77], Fernandes et al [78], Higgins III and Becker [79], Preyde et al [81], and Rehmani and Amatullah [82]. The application of six sigma [93], PDSA cycle [84,85], and ED dashboard/reporting application [98] were also detected in the literature as part of the multiple quality-based methods that have been applied for solving the excessive LOS problem in EDs.…”
Section: Papers Focusing On Reducing the Extended Losmentioning
confidence: 99%
“…The most recent work employing QI is cited in Lovett et al [80] who reported an intervention at a multi-campus academic health system where immediate improvements were enhanced in relation to LOS. Other works employing QI can be seen in Brent et al [76], Fernandes and Christenson [77], Fernandes et al [78], Higgins III and Becker [79], Preyde et al [81], and Rehmani and Amatullah [82]. The application of six sigma [93], PDSA cycle [84,85], and ED dashboard/reporting application [98] were also detected in the literature as part of the multiple quality-based methods that have been applied for solving the excessive LOS problem in EDs.…”
Section: Papers Focusing On Reducing the Extended Losmentioning
confidence: 99%
“…Standardized template forms with compliance guidelines have been used to enhance compliance and increase billable income by appropriately representing the care provided. 2,3 Templates permit reproducible and consistent documentation by health care providers at multiple levels and can be easily modified to fit a specific patient population or service area.…”
mentioning
confidence: 99%